Medicine for global health: can “simple interventions” improve the worldwide burden of disease? - Birbeck, Gretchen (BioMed Central, 2013)
Improvements to medical practice and delivery of treatment has been the focus of many international collaborations aiming to address the delivery of appropriate health care in low- and middle-income countries. However, this is compounded by various social, cultural as well as resource allocation issues. This Editorial marks the launch of an article collection on Medicine for Global Health (http://www.biomedcentral.com/bmcmed/series/medicine_for_global_health), and here, guest editor Gretchen Birbeck discusses the challenges, importance and increasing relevance of global health.